Hybridization and a loss of sex shape genome‐wide diversity and the origin of species in the evening primroses (Oenothera, Onagraceae). Issue 3 (5th August 2019) - Hollister, Jesse D.; Greiner, Stephan; Johnson, Marc T. J.; Wright, Stephen I.
Summary: Hybridization is thought to promote speciation in at least two ways – by fixation of heterozygosity from diploid progenitors in allopolyploids, and by generation of transgressive phenotypes and shifting fitness optima during homoploid hybrid speciation. While recent studies support a hybrid origin for a growing number of species, the extent to which hybrid origins shape patterns of diversity in asexual species remains underexplored. Here we employed transcriptome sequencing and population genomic analysis to describe patterns of genomic variation in the 13 species belonging to Oenothera subsection Oenothera . Eight of these species are functionally asexual and arose by hybrid speciation from parents spanning a range of phylogenetic divergence. We showed that genomic divergence between parents has been retained as heterozygosity in functionally asexual species, and that genome‐wide levels of heterozygosity in these asexuals largely reflects the divergence of parental haplotypes coupled with a breakdown in recombination and segregation across the genome. These results show that divergence between parental species and loss of sex in hybrids shape patterns of whole‐genome diversity and the origin of asexual species.